Run to Quit: Program design and evaluation protocol. (October 2016) - Priebe, Carly S.; Atkinson, John; Faulkner, Guy
Highlights: A multi-layer intervention is designed to target smoking cessation and activity. Running groups across the country are utilized to promote behaviour change. The evaluation aims to understand the feasibility of this real-world intervention. A mixed-methods approach will be utilized to understand program's various facets.